Patient and Trauma Center Characteristics Associated With Helicopter Emergency Medical Services Transport for Patients With Minor Injuries in the United States. (November 2014) - Cheung, Brian H.; Delgado, M. Kit; Staudenmayer, Kristan L.; Meisel, Zachary
Abstract Background Helicopter emergency medical services (EMS) transport is expensive, and previous work has shown that cost‐effective use of this resource is dependent on the proportion of minor injuries flown. To understand how overtriage to helicopter EMS versus ground EMS can be reduced, it is important to understand factors associated with helicopter transport of patients with minor injuries. Objectives The aim was to characterize patient and hospital characteristics associated with helicopter transport of patients with minor injuries. Methods This was a retrospective analysis of adults ≥18 years who were transported by helicopter to Level I/II trauma centers from 2009 through 2010 as identified in the National Trauma Data Bank. Minor injuries were defined as all injuries scored at an Abbreviated Injury Scale (AIS) score of <3. Patient and hospital characteristics associated of being flown with only minor injuries were compared in an unadjusted and adjusted fashion. Hierarchical, multivariate logistic regression was used to adjust for patient demographics, mechanism of injury, presenting physiology, injury severity, urban–rural location of injury, total EMS time, hospital characteristics, and region. Results A total of 24, 812 records were identified, corresponding to 76, 090 helicopter transports. The proportion of helicopter transports with only minor injuries was 36% (95% confidence interval [CI] = 34% to 39%). Patient characteristics associated with being flown with minor injuries included being uninsured (odds ratio [OR] = 1.36, 95% CI = 1.26 to 1.47), injury by a fall (OR = 1.32, 95% CI = 1.20 to 1.45), or other penetrating trauma (OR = 2.52, 95% CI = 2.12 to 3.00). Being flown with minor injuries was more likely if the patient was transported to a trauma center that also received a high proportion of patients with minor injuries by ground EMS (OR = 1.89, 95% CI = 1.58 to 2.26) or a high proportion of EMS traffic by helicopter (OR = 1.35, 95% CI = 1.02 to 1.78). No significant association with urban–rural scene location or EMS transport time was found. Conclusions Better recognizing which patients with falls and penetrating trauma have serious injuries that could benefit from being flown may lead to the more cost‐effective use of helicopter EMS. More research is needed to determine why patients without insurance, who are most at risk for high out‐of‐pocket expenses from helicopter EMS, are at higher risk for being flown when only having minor injuries. This suggests that interventions to optimize cost‐effectiveness of helicopter transport will likely require an evaluation of helicopter triage guidelines in the context of regional and patient needs.